2015
DOI: 10.1007/s11211-015-0242-x
|View full text |Cite
|
Sign up to set email alerts
|

Distributive Justice Antecedents of Race and Gender Disparities in First-Year College Performance

Abstract: Public education is a sphere of society in which distributive justice with respect to the allocation of opportunities to learn can have profound and lasting effects on students' educational outcomes. We frame our study in the distributive justice literature, and define just outcomes specifically from a meritocratic and strict egalitarian perspectives in order to investigate how assignment to academic tracks and the availability of opportunities to learn during high school are associated with students' academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 64 publications
2
8
0
Order By: Relevance
“…Our findings suggest that there might be an interplay between students' race and the racial composition of the school context (consistent with Bottia, Mickelson, Giersch, Stearns, & Moller, ; Newton, ), which determines the timing of when the influence of attending a school with predominantly White students will come into effect. This finding is also consistent with previous literature that recognizes the major role race has in the STEM experiences of Black students and professionals involved in STEM fields (Brown et al, ).…”
Section: Discussionsupporting
confidence: 80%
“…Our findings suggest that there might be an interplay between students' race and the racial composition of the school context (consistent with Bottia, Mickelson, Giersch, Stearns, & Moller, ; Newton, ), which determines the timing of when the influence of attending a school with predominantly White students will come into effect. This finding is also consistent with previous literature that recognizes the major role race has in the STEM experiences of Black students and professionals involved in STEM fields (Brown et al, ).…”
Section: Discussionsupporting
confidence: 80%
“…Poor behavioral climates likely affect instruction directly by reducing time on task and engagement (Brophy, 1983;Simonsen et al, 2008) but also indirectly by eroding teacher commitment and effort (Collie et al, 2012). Second, curricular offerings and assignment processes can vary greatly across secondary schools (Bottia et al, 2015;Kelly & Price, 2011;Klopfenstein, 2004;Yun & Moreno, 2006). For example, comparing clusters of schools in California, Yun and Moreno (2006) found that schools serving low-poverty, predominantly Asian and White students offered an average of 11.6 AP courses compared to less than 5 in schools serving high poverty Latino and Black students.…”
Section: School Organizational Functioningmentioning
confidence: 99%
“…Specifically, they found that girls were more likely to perceive gender and racial equality; however, they are less likely to observe educational inequities than boys. As Bottia, Giersch, Mickelson, Stearns, and Moller (2016) assert, understanding this precollege context is valuable in rethinking higher education’s role in social justice education.…”
Section: Defining Social Justicementioning
confidence: 99%